PENGARUH TINGKAT SUKU BUNGA DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM - Wulansari, Ria; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of interest rates, current ratio, total assets turnover, debt to equity ratio, return on assets, return on equity, earnings per share to the stock return. The sample are all companies which are listed in LQ 45 index in Indonesia Stock Exchange from 2012 to 2014. The analysis technique has been done by using multiple linear regressions analysis, model feasibility test (F test), multiple determination coeficients, and t-test. Based on the result of the research it has been found that the interest rate, total assets turnover, and debt to equity ratio has negative influence and insignificant to the stock price because the value of negative coefficient regressions and the significant value of t test is larger than 0,05. Current ratio, return on assets, and return on equity has signficant and positive influence to the stock return because the value of positive coefficient regressions and the significant value of t test is smaller than 0,05. earnings per share does not have any significant but positive influence to the stock price because the value of positive coefficient regressions and the significant value of t test is larger than 0,05.Keywords: interest rates, financial performance, stock return